Organisational climate and change‐orientated behaviour: The mediating effects of employee learning culture and perceptions of performance appraisal - Gil, Alfonso J.; Mataveli, Mara; Garcia‐Alcaraz, Jorge L.; Ibanez‐Somovilla, Laura (European management review, 2024)
The characteristics of the working environment, particularly organisational climates, serve as fundamental tools for interpreting change‐orientated behaviour. However, examining employees' norms and attitudes would help clarify the guidelines for supporting organisational change. The present study has two objectives: first, to analyse the effect of organisational climate on change‐orientated behaviour, and secondly, to analyse the multiple mediation effect of both employee learning culture and perceptions of performance appraisal between the organisational climate and change‐orientated behaviour. A questionnaire was distributed to a sample of 359 employees in Spain. The research model was tested using partial least squares structural equation modelling. Organisational climate was found to have a positive effect on change‐orientated behaviour. Employee learning culture and perceptions of performance appraisal also partly mediated organisational climate and change behaviour. This work shows the importance of organisational climates in the development of employees' behaviour towards change.